Antiviral Responses in Mouse Embryonic Stem Cells: DIFFERENTIAL DEVELOPMENT OF CELLULAR MECHANISMS IN TYPE I INTERFERON PRODUCTION AND RESPONSE - Wang, Ruoxing (American Society for Biochemistry and Molecular Biology, 2014)
We have recently reported that mouse embryonic stem cells (mESCs) are deficient in expressing type I interferons (IFNs) in response to viral infection and synthetic viral RNA analogs (Wang, R., Wang, J., Paul, A. M., Acharya, D., Bai, F., Huang, F., and Guo, Y. L. (2013) J. Biol. Chem. 288, 15926–15936). Here, we report that mESCs are able to respond to type I IFNs, express IFN-stimulated genes, and mediate the antiviral effect of type I IFNs against La Crosse virus and chikungunya virus. The major signaling components in the IFN pathway are expressed in mESCs. Therefore, the basic molecular mechanisms that mediate the effects of type I IFNs are functional in mESCs; however, these mechanisms may not yet be fully developed as mESCs express lower levels of IFN-stimulated genes and display weaker antiviral activity in response to type I IFNs when compared with fibroblasts. Further analysis demonstrated that type I IFNs do not affect the stem cell state of mESCs. We conclude that mESCs are deficient in type I IFN expression, but they can respond to and mediate the cellular effects of type I IFNs. These findings represent unique and uncharacterized properties of mESCs and are important for understanding innate immunity development and ESC physiology.